1990
DOI: 10.1148/radiology.176.3.2202013
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous pediatric renal biopsy: use of the biopsy gun.

Abstract: A recently developed biopsy gun was used in the ultrasound (US)-guided biopsy of native kidneys in seven children. The biopsy gun employs a needle (18 gauge) smaller than that usually used for renal biopsies. In all seven cases it provided a core biopsy specimen that contained enough glomeruli to make a definitive histologic diagnosis of renal parenchymal disease. Use of the biopsy gun eliminated the more complicated movements needed to obtain samples with the conventional manual biopsy techniques. No major co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Our experience needs to be compared with other studies applying the different needles for renal biopsy. Successful application of the Biopty device has been demonstrated in adults [19, 20] and children [14, 15, 21], but those studies comparing the efficacy of the Biopty gun with that of other needles yielded conflicting results, ranging from no change in efficacy observed in adults [20] and children [22] to an improved rate of retrieval of glomeruli [19]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our experience needs to be compared with other studies applying the different needles for renal biopsy. Successful application of the Biopty device has been demonstrated in adults [19, 20] and children [14, 15, 21], but those studies comparing the efficacy of the Biopty gun with that of other needles yielded conflicting results, ranging from no change in efficacy observed in adults [20] and children [22] to an improved rate of retrieval of glomeruli [19]. …”
Section: Discussionmentioning
confidence: 99%
“…This change reflects growth and spatial distribution of glomeruli in the first years of life and is in keeping with previous comparisons of biopsies in adults and children. In children <10 years of age the number of glomerular sections per square millimeter of renal cortex is more than 100% higher than in adults [15, 31]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have confirmed the effectiveness of these biopsy "guns" for obtaining high quality histopathologic specimens from the liver, kidney, and pancreas [2][3][4][5]. A controlled trial proved the superiority of automated devices over conventional biopsy needles for abdominal puncture [6].…”
Section: Automated Biopsy Devices Were Introduced In 1982 Bymentioning
confidence: 94%
“…Other authors [9] also reported a low incidence of this minor complication, though other minor complications like local pain or discomfort are not uncommon [6]. In patients with coagulation defects the risk of postbiopsy bleeding can be reduced by fresh frozen plasma infusion and vitamin K. Various sizes and types of needles have been used by different authors [4,10,11] with the aim to minimize bleeding complications. We used 14 G and 18 G Tru-cut needles with exact positioning of the needles under ultrasound guidance and found both equally safe and effective with no major complication.…”
Section: Discussionmentioning
confidence: 99%